Social Media Instagram for Promoting Tourism In The Eastern Indonesia - Kusumasari, Adita Ayu; Syafitri, Annisa Amelia; Selly, Adita Febiola; Buseri, Dimas Prastyo; Erlangga, Fabyan Raif; Jimenez, Genett (Bulletin of Social Informatics Theory and Application, 2022)
Indonesia consists of many islands and cultures, so there are many tourist destinations in Indonesia. It is appropriate to introduce tourism in Indonesia by having various tourism destinations. Many methods can be used to introduce Indonesian tourist objects, including current social media that can also be used to promote tourism. This study aims to reveal the influence of social media as a tourism promotion in the eastern part. In this paper, Instagram is the social media focused on researching eastern tourism promotion. Social media Instagram has a large number of users. Currently, the number of Instagram downloads is 1 billion. In this paper, data collection on Instagram accounts that have tourism promotion content will be carried out. Data taken, such as the number of followers and the number of posts, then an account will be determined, which will be the object of research so that later it will produce an analysis of how the Instagram account promotes tourism. Indonesia complies with the elements of the 7C framework